Electrospun PCL/PVP nanofibers embedded with magnetic nanoparticles: Correlating porosity, structure and magneto-thermo-mechanical properties - Pekdemir, Sibel Selcuk; Pekdemir, Mustafa Ersin; Ulu, Ahmet; Kuzu, Serpil Yalcin (Elsevier, 2026)
Smooth and homogeneous PCL/PVP-Fe3O4 composite nanofibers with varying magnetic nanoparticle (MNP) contents were successfully fabricated via a simple electrospinning technique. The influence of Fe3O4 MNP incorporation on the structural, morphological, thermal, magnetic, and physicochemical properties of PCL/PVP nanofibers was systematically investigated using ATR-IR, TGA, DTA, SEM, EDX, XRD, and VSM analyses. ATR-IR and XRD results revealed strong interactions between Fe3O4 and the polymer matrix, indicating significant structural modification and enhanced crystallinity. The optimized nanofibers exhibited uniform diameters (400-600 nm) and smooth, interconnected surfaces, confirming the efficiency of the electrospinning parameters. EDX mapping verified the homogeneous distribution of Fe3O4 MNPs across the nanofibers. The incorporation of Fe3O4 notably improved the thermal stability and magnetic response, achieving a saturation magnetization of 5.30 emu/g at 10 wt% Fe3O4 content. Moreover, the presence of rigid inorganic particles enhanced mechanical stability while slightly reducing swelling behavior due to restricted polymer chain mobility. Overall, the synergistic effects of PCL/PVP blending and Fe3O4 loading produced nanofibers with balanced thermal, magnetic, and mechanical performance. The results suggest that optimizing the thermal, magnetic, and mechanical properties of PCL/PVP- Fe3O4 composite nanofibers can endow them with versatile functional material potential.
Keywords: Fe 3 O 4 magnetic nanoparticles; PCL/PVP blend; Electrospinning; Thermal stability; Magnetic properties